2018
DOI: 10.1128/aem.00795-18
|View full text |Cite
|
Sign up to set email alerts
|

Single-Homology-Arm Linear DNA Recombination by the Nonhomologous End Joining Pathway as a Novel and Simple Gene Inactivation Method: a Proof-of-Concept Study in Dietzia sp. Strain DQ12-45-1b

Abstract: Nonhomologous end joining (NHEJ) is critical for genome stability because of its roles in double-strand break repair. Ku and ligase D (LigD) are the crucial proteins in this process, and strains expressing Ku and LigD can cyclize linear DNA Here, we established a proof-of-concept single-homology-arm linear DNA recombination for gene inactivation or genome editing by which cyclization of linear DNA by NHEJ could be used to generate nonreplicable circular DNA and could allow allelic exchanges between the circula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Therefore, errors that are prone to occur in NHEJ are not errors that occur at the outset. In fact, NHEJ is a key strategy for stabilizing the genome, which plays an important role in the repair of DSBs (Lu et al, 2018). Although HDR is more accurate, it has a specific cycle limit.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, errors that are prone to occur in NHEJ are not errors that occur at the outset. In fact, NHEJ is a key strategy for stabilizing the genome, which plays an important role in the repair of DSBs (Lu et al, 2018). Although HDR is more accurate, it has a specific cycle limit.…”
Section: Discussionmentioning
confidence: 99%
“…We utilized three kinds of media for cultivating Dietzia sp. DQ12‐45‐1b and its mutant strains in this study: (i) GPY medium (glucose, 10 g/l, yeast extract 5 g/l and tryptone 10 g/l) was used to harvest the cell biomass of DQ12‐45‐1b, Δ DtmbtB and Δ DtmbtB :: DtmbtB , (ii) MFN medium, composed of minimal medium [MF medium, Na 2 HPO 4 ·12H 2 O 17.9 g/l, NaH 2 PO 4 ·2H 2 O 7.8 g/l, (NH 4 ) 2 SO 4 5 g/l, KCl 5 g/l, MgSO 4 ·7H 2 O 0.2 g/l, CaCl 2 0.05 g/l, ZnSO 4 ·7H 2 O 0.1 mg/l, MnCl 2 ·4H 2 O 0.03 mg/l, H 3 BO 3 0.3 mg/l, CoCl 2 ·6H 2 O 0.2 mg/l, CuCl 2 ·2H 2 O 0.01 mg/l, NiCl 2 ·6H 2 O 0.02 mg/l, Na 2 MoO 4 ·2H 2 O 0.03 mg/l, pH 8.0] and 5 g/l sodium acetate (NaAc) was used to grow DQ12‐45‐1b amended with different types of MVs (Lu et al ., 2018) and (iii) MFNI medium, MFN medium amended with 8 μM FeCl 3 was used for cultivation of DQ12‐45‐1b and its mutant strains to generate the iron‐limiting condition, and isolation of their MVs. The incubation of DQ12‐45‐1b was all conducted at 30°C, 150 rpm.…”
Section: Methodsmentioning
confidence: 99%
“…Bacterial NHEJ systems have been less extensively studied [14][15][16] . Fortunately, NHEJ systems are present in a diverse group of bacteria, from Mycobacterium tuberculosis to Pseudomonas aeruginosa, and some systems have been used for engineering in their native context 17,18 . Relatively little work has been done to express these systems heterologously, but one study showed NHEJ was able to circularize transformed linear DNA in E. coli 19 and another E. coli study showed NHEJ can repair DSBs caused by Cas9 12 .…”
Section: Poakmentioning
confidence: 99%